The Influence Of Service Quality, Price Perceptions, And Marketing Communications On Customer Satisfaction PT Borobudor OTO Mobil Mitsubishi - Rinandi Ryski Hartanto (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study aimed to investigate the influence of service quality, price perceptions, and marketing communications on customer satisfaction at PT Borobudur OTO Mobil Mitsubishi. A total of 100 respondents, who were customers of PT Borobudur OTO Mobil Mitsubishi, participated in the study. Data collection was conducted through a questionnaire, and the collected data were analyzed using SPSS 22. The demographic characteristics of the respondents were initially analyzed, revealing that 76% were male and 24% were female. The majority of the customers (45%) fell within the age group of 31-40 years, and education-wise, 45% held a bachelor's degree, 38% had a diploma degree, and 17% had a high school education. The study then examined the variables of service quality, perception of price, and marketing communication. The customers rated the quality of service provided by PT Borobudur OTO Mobil Mitsubishi as satisfactory, with an average score of 4.50. Similarly, the customers had positive perceptions of the price of PT Borobudur OTO Mobil Mitsubishi's products, as indicated by an average score of 4.29. Furthermore, the customers perceived the marketing communication efforts of PT Borobudur OTO Mobil Mitsubishi as effective, with an average score of 4.39. A validity test was conducted to ensure the research instrument's reliability, which confirmed the validity of the questionnaire for further analysis. In conclusion, the study revealed that the customers of PT Borobudur OTO Mobil Mitsubishi were generally satisfied with the quality of service, had positive perceptions of the price, and perceived the marketing communication efforts as effective. These findings provide valuable insights for PT Borobudur OTO Mobil Mitsubishi to enhance customer satisfaction and refine its marketing strategies.